Who is eating fructose within the Aedes albopictus gut microbiota?. (23rd January 2020) - Guégan, Morgane; Tran Van, Van; Martin, Edwige; Minard, Guillaume; Tran, Florence‐Hélène; Fel, Benjamin; Hay, Anne‐Emmanuelle; Simon, Laurent; Barakat, Mohamed; Potier, Patrick; Haichar, Feth el Zahar; Valiente Moro, Claire
Summary: The Asian tiger mosquito Aedes albopictus is a major public health concern because of its invasive success and its ability to transmit pathogens. Given the low availability of treatments against mosquito‐borne diseases, vector control remains the most suitable strategy. The methods used thus far are becoming less effective, but recent strategies have emerged from the study of mosquito‐associated microorganisms. Although the role of the microbiota in insect biology does not require further proof, much remains to be deciphered in mosquitoes, especially the contribution of the microbiota to host nutrient metabolism. Mosquitoes feed on plant nectar, composed of mostly fructose. We used stable isotope probing to identify bacteria and fungi assimilating fructose within the gut of Ae. albopictus . Mosquitoes were fed a 13 C‐labelled fructose solution for 24 h. Differences in the active microbial community according to the sex of mosquitoes were highlighted. The bacterium Lelliottia and the fungi Cladosporium and Aspergillus dominated the active microbiota in males, whereas the bacterium Ampullimonas and the yeast Cyberlindnera were the most active in females. This study is the first to investigate trophic interactions between Ae. albopictus and its microbiota, thus underscoring the importance of the microbial component in nectar feeding in mosquitoes.